SOCIAL FACTORS THAT CONTRIBUTE TO THE SUCCESS OF THE ELDERLY POSYANDU PROGRAM IN THE WORKING AREA OF THE SADABUAN HEALTH CENTER, PADANG SIDIMPUAN CITY - Primastuti, Hannisa; Ahmad, Haslinah; Antoni, Adi (LPPM Univ. Ibn Khaldun Bogor, 2026)
Posyandu Elderly program in the working area of the Sadabuan Health Center, Padangsidimpuan City. The increase in the number of the elderly along with the increase in life expectancy requires optimal and sustainable health services. This study uses a quantitative approach with an analytical descriptive design. The study population is all elderly people who are registered as participants of the Elderly Posyandu, with samples taken using stratified random sampling techniques. Data collection was carried out through questionnaires, semi-structured interviews, observations, and documentation studies. Data analysis was carried out using SPSS through descriptive and inferential analysis. The results of the study showed that the level of education of the elderly did not have a significant effect on the level of participation in Posyandu Elderly activities. On the other hand, family support, social interaction of the elderly, and activities of health cadres have an influence on the success of program implementation. Elderly people who receive family support and have good social interaction tend to be more active in participating in activities. The active role of cadres also increases the effectiveness of services. It was concluded that social factors have an important role in supporting the success of the Elderly Posyandu, so it is necessary to strengthen family support and empower health cadres in a sustainable manner.